The Concept of al-Ittihad: Abu Yazid al-Busthami's Thought and its Relevance in Sufism - Yogi Fery Hidayat (Journal of Noesantara Islamic Studies, 2024)
This research aims to examine the concept of al-Ittihad in the thought of Abu Yazid al-Busthami and its relevance within the tradition of Sufism, particularly in the context of Islamic spirituality. Al-Ittihad refers to the mystical union between human and God, where a Sufi feels a dissolution into the Divine during a profound spiritual experience. This concept is considered one of the central themes in Sufism but often sparks theological controversy among orthodox scholars, especially since it is perceived as violating the principle of tauhid (the oneness of God). Through shathiyat (mystical utterances) such as "Glory be to Me," Abu Yazid expressed his experiences in the states of fana' (annihilation of the self) and baqa' (subsistence in God), which form the core of his mystical journey towards al-Ittihad. This study employs a literature review method by analyzing classical Sufi texts and scholars' interpretations regarding this concept. Additionally, it explores the relevance of al-Ittihad in the modern context, where Sufism has seen a revival of interest among both Muslims and non-Muslims as a response to the spiritual quest in the face of modern challenges. The research findings indicate that although al-Ittihad is often misunderstood and debated, it remains a significant aspect of the spiritual journey in Sufism. The experience of al-Ittihad offers a way to deepen one's relationship with God through the dissolution of ego and worldly attachments, and it plays a crucial role in modern Sufi studies as a means of achieving profound spiritual intimacy.